PENINGKATAN PENGETAHUAN MASYARAKAT KAMPUS MELALUI EDUKASI ONLINE TENTANG MEKANISME COVID-19 - Mulyani, Erry Yudhya; Pamungkas, Rian Adi; Ummanah, Ummanah; Arrozi, Muhammad Fachruddin; Saputra, Sugiyono (Universitas Esa Unggul, 2020)
There were 23,851 Covid-19 cases in Indonesia at the end of May 2020, with a death rate of 1,473. Coronavirus is a group of viruses that can cause disease in animals or humans. Covid-19 is a contagious disease, with a new type of virus that occurred in Wuhan, China, in December 2019. The purpose of this activity is to increase knowledge and demeanour about the mechanism of Covid-19 as an effort to prevent the Covid-19 disease. The method of activity is carried out with socialization (lecture) and FGD (Forum Group Discussion). The target of this activity is the campus community consisting of staff-bureaus, lecturers, and the rest of the university staff. The number of participants who participated was 79 people. Most were from the faculty of law (21.5%), health sciences (21.5%), psychology (21.5%), and computer science (16.5%). The results of the socialization showed that most participants understood about the Covid-19 mechanism; knowledge (good) 67.1% and attitude (positive) 59.5%. The results of the FGD showed that participants mainly discussed the dangers of the virus (transmission mechanism, virus resistance, ways of working) (52.4%), prevention efforts (23.8%), infected subjects (14.3%) and the Covid-19 symptoms (9.5%). As many as 92.0% expressed an understanding and tried to prevention based on information provided. This activity increased knowledge about the Covid-19 mechanism in preventing transmission by 24.9%. Thus, it is important to carry out an educational activities especially with online methods routinely and periodically in an effort to increase knowledge regarding the conditions of the pandemic. Ã‚Â Keywords: Online Education, Covid-19, Knowledge